Das materielle Computerstrafrecht - Bergauer, Christian (Jan Sramek Verlag, 2016)
The aims of the present study are to describe the modern forms of cybercrime and analyze the substantive computer-specific offences of the Austrian Penal Code by the means of specialist literature and - as available - relevant judgments. Based on the debate about the terms "cybercrime" or "computer criminal law" and the term of data in the Austrian Penal Code, the specific substantive computer-specific offences, including the penal provision of the Data Protection Code concerning the criminal protection of personal data, are presented and discussed systematically.